Curso de Pedagogia UAB-Unimontes: caderno didático em foco - Maria Auxiliadora Amaral Silveira Gomes (2015)
Analysis of instructional materials in use in the context of Distance Education - Distance Education of the Pedagogy Course at the State University of Montes Claros - Unimontes, offered through the Open University System of Brazil - UAB. This research aims to analyze the instructional materials named teaching material produced to teach two subjects in the Pedagogy course in the context of distance education - UAB/Unimontes, seeking to understand the implications of the didactic proposal in use. We chose a qualitative methodological approach that enables a critical reflection on the teaching material in use and which facilitates a greater understanding of the process and the educational context in which this material is part of. The Theory of Content analysis and the theory of discourse analysis support the analyses, supporting reflection and critical understanding of the material in the context of teaching and learning investigated. Besides the bibliographic and document research, we use direct observation of classroom time of the subject; analysis of forums and chats of the subjects in the Virtual Learning Environment - VLE, where subjects are virtually developed; questionnaires and interviews with students that will be conducted to a group of students to clarify some of the highlighted issues of the answers collected in the questionnaires which require further explanation. For a deeper understanding of this teaching modality, distance education in Brazil is initially contextualized with the history of the Open University System creation in Brazil UAB and as consolidation of public policy for the expansion of higher education in Brazil. In a second phase, we highlight the technological tools used in undergraduate courses in the distance education modality, highlighting the main tool used in courses taught by UAB / Unimontes, which is the teaching material, the object of this research as well as the process of production of this material by content professors and its use by the students and university teacher educators. And finally, we analyze the teaching material produced for two chosen subjects: Company Pedagogy and Physical Activity, Recreation and Games, evaluating: their structure (according to guidelines developed by UAB / Unimontes to produce this material); the effectiveness of this material in the development of the subject based on the students speech and the observation of the classroom meetings and records of forums and chats, during the subjects teaching and, finally, by students interviews to understand issues related to training in distance learning modality. It is expected that the specific context of this study may contribute to greater understanding of the production and use of teaching material for distance education and that the research results provide a contribution to the pedagogical practice in distance education courses.